2017
DOI: 10.1186/s13054-017-1839-2
|View full text |Cite
|
Sign up to set email alerts
|

Blind bedside postpyloric placement of spiral tube as rescue therapy in critically ill patients: a prospective, tricentric, observational study

Abstract: BackgroundVarious special techniques for blind bedside transpyloric tube placement have been introduced into clinical practice. However, transpyloric spiral tube placement facilitated by a blind bedside method has not yet been reported. The objective of this prospective study was to evaluate the safety and efficiency of blind bedside postpyloric placement of a spiral tube as a rescue therapy subsequent to failed spontaneous transpyloric migration in critically ill patients.MethodsThis prospective, tricentric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 38 publications
2
30
0
3
Order By: Relevance
“…We read with great interest the recent report on blind bedside postpyloric placement by Lv et al [ 1 ]. Their methods were proven to be safe and effective in intensive care units.…”
mentioning
confidence: 99%
“…We read with great interest the recent report on blind bedside postpyloric placement by Lv et al [ 1 ]. Their methods were proven to be safe and effective in intensive care units.…”
mentioning
confidence: 99%
“…Recently, a novel NET with a spiral tip for post-pyloric placement in the assistance of prokinetic agents has emerged as a promising approach [18,[34][35][36], as demonstrated by the subgroup results strati ed by spiral or straight tube tip. In previous studies, Lai et al demonstrated that a spiral NET in conjunction with metoclopramide is preferable to a straight NET for post-pyloric placement [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent letter published in Critical Care [1], Sun and colleagues argued that the choice of a postpyloric tube and the patient’s position with regard to spiral nasojejunal feeding tube insertion in a previously published study [2] required further improvement.…”
mentioning
confidence: 99%
“…We are willing to make a comparison between the two positions in future work and optimize the method of remedial spiral feeding tube insertion. One position is described in the authors’ work [1], another position is described in our previous published work [2]. …”
mentioning
confidence: 99%
See 1 more Smart Citation